2016
DOI: 10.1093/infdis/jiw100
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of Complement and CD14 Attenuates Bacteria-Induced Inflammation in Human Whole Blood More Efficiently Than Antagonizing the Toll-like Receptor 4–MD2 Complex

Abstract: Background. Single inhibition of the Toll-like receptor 4 (TLR4)–MD2 complex failed in treatment of sepsis. CD14 is a coreceptor for several TLRs, including TLR4 and TLR2. The aim of this study was to investigate the effect of single TLR4-MD2 inhibition by using eritoran, compared with the effect of CD14 inhibition alone and combined with the C3 complement inhibitor compstatin (Cp40), on the bacteria-induced inflammatory response in human whole blood.Methods. Cytokines were measured by multiplex technology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…shown to interact with CD14 [63]. Recently, eritoran was compared with a neutralizing anti-CD14 antibody in a human whole-blood model with respect to effect on Gram-negative and -positive, bacteria-induced inflammation [64]. In line with previous findings, eritoran and anti-CD14 mostly inhibited Gramnegative-induced inflammation, whereas Gram-positive inflammation was more complement dependent, possibly explaining the lack of effects of eritoran in a broad sepsis population.…”
Section: Tlr Inhibitionsupporting
confidence: 59%
“…shown to interact with CD14 [63]. Recently, eritoran was compared with a neutralizing anti-CD14 antibody in a human whole-blood model with respect to effect on Gram-negative and -positive, bacteria-induced inflammation [64]. In line with previous findings, eritoran and anti-CD14 mostly inhibited Gramnegative-induced inflammation, whereas Gram-positive inflammation was more complement dependent, possibly explaining the lack of effects of eritoran in a broad sepsis population.…”
Section: Tlr Inhibitionsupporting
confidence: 59%
“…CD14 not only transfers the identified lipoprotein signal to TLR2 but also transfers the identified LPS signal to TLR4. 55 Our data showed that silencing of TLR2 inhibits cell death, but silencing of TLR4 fails to inhibit cell death, suggesting that the Tp92 protein induces THP-1 cell death via CD14 and/or TLR2. A study showed that TLR2 activates the inflammasome NLRP3, 56 but there has been no report on whether TLR2 activates NLRC4 and mediates atypical pyroptosis.…”
Section: Control Rosup Tp92mentioning
confidence: 59%
“…In addition, anti‐CD14 Ab treatment completely inhibits cell death, and anti‐TLR2 Ab treatment partially inhibits cell death. CD14 not only transfers the identified lipoprotein signal to TLR2 but also transfers the identified LPS signal to TLR4 . Our data showed that silencing of TLR2 inhibits cell death, but silencing of TLR4 fails to inhibit cell death, suggesting that the Tp92 protein induces THP‐1 cell death via CD14 and/or TLR2.…”
Section: Discussionmentioning
confidence: 74%
“…8,10 The importance of revisiting this issue lies in the clinical relevance of C being or not being involved in infusion reactions, since C-based predictive assays and C-inhibitionbased preventive measures are still open, largely unexplored options in combating these adverse immune reactions. 27 Inhibition of C activation as adjunct therapy against acute life-threatening immunoactivation is getting increasing recognition, [28][29][30] so premature or unfounded exclusion of C activation as a key contributing mechanism of infusion reactions may be misleading in this field. The original observations giving rise to questioning the role of C in the significant pulmonary hypertensive effect of 500 nm spherical PS-NPs in pigs was the lack of C activation in hirudinized pig whole blood in vitro.…”
Section: Discussionmentioning
confidence: 99%